Socio-demographic and disease related characteristics associated with unplanned emergency department visits by cancer patients: a retrospective cohort study - Polly H. Dufton; Allison Drosdowsky; Marie F. Gerdtz; Mei Krishnasamy (BMC, 2019)
Abstract Background Emergency department (ED) presentations made by patients having cancer treatment are associated with worse outcomes. This study aimed to explore the socio-demographic and disease related characteristics associated with ED presentation, frequent ED presentations, and place of discharge for cancer patients receiving systemic cancer therapies in the ambulatory setting. Methods This was a single site, retrospective observational cohort design. Hospital data for patients treated in the Day Oncology Unit of a large public tertiary hospital in Melbourne, Australia between December 2014 and November 2017 were extracted from clinical databases and retrospectively matched to ED attendance records. Andersen's Behavioral Model of Health Service Utilisation provided the conceptual framework for exploring associations between socio-demographic and disease characteristics and ED use. Results A total of 2638 individuals were treated in the Day Oncology Unit over the study dates. Of these, 1182 (45%) made an unplanned ED presentation within 28 days of receiving systemic cancer therapy. One hundred and twenty-two (12%) patients attended the ED on two or more occasions within 28 days; while 112 (10%) patients attended the ED four or more times (within 28 days of receiving systemic cancer therapy) within any given 12 month period. Being born outside of Australia was independently related to making an unplanned ED presentation within 28 days of receiving anti-cancer therapy (p < .01) as was being diagnosed with head and neck (p = .03), upper gastrointestinal (p < .001), colorectal (p < .001), lung (p < .001), skin (p < .001) or breast cancer (p = .01). Conclusions This study identified a subgroup of cancer patients for whom an ED presentation is more likely. Better understanding of socio-demographic and disease related characteristics associated with the risk of an ED presentation may help inform targeted follow up of patients, to mitigate potentially avoidable ED presentation and optimize outcomes of care.